Obesity, subliminal perception and inhibition: Neuromodulation of the prefrontal cortex. (August 2019) - Osimo, Sofia Adelaide; Korb, Sebastian; Aiello, Marilena
Abstract: The prefrontal cortex (PFC) plays a central role in food choice, and may be partly dysfunctional in obesity – a condition linked to altered attention and inhibition processes, particularly in response to food-related stimuli. We investigated the role of the PFC in subliminal visual processing and response inhibition to food pictures using anodal, cathodal, or sham transcranial direct current stimulation (tDCS) in a sample of 53 normal weight, overweight, or obese participants. Subliminal processing was measured with a breaking continuous flash suppression task (bCFS), and inhibition with a Go/No-Go task. BMI was included in the analyses as a continuous predictor. Higher BMI was associated with prolonged subliminal processing for both food and nonfood pictures in the bCFS task, and with longer RTs in food Go trials in the Go/No-Go task. Therefore, higher BMI was associated with an attentional bias for food images during supraliminal, but not subliminal visual processing. Moreover, anodal tDCS resulted in shorter detection times in the bCFS task, especially in participants with higher BMI. We conclude that anodal tDCS affects subliminal perception and attentional processes, and speculate that these effects may explain previous reports of reduced craving and food intake after anodal tDCS. Highlights: Obesity was associated with an increased threshold of perceptual awareness An attentional bias for food in obesity is only present at a late stage of stimulus processing Anodal stimulation improves attentional performance, especially in participants with higher BMIs